Coinage metal amido and thiolate SNS complexes: consequences of catalyst speciation in Cu(i)-catalysed carbonyl hydroboration. Issue 27 (17th March 2023) - Ataie, Saeed; Lohoar, Maxwell; Mangin, Loïc P.; Baker, R. Tom
Abstract : Three new IPr-Ag- and -Au-SNS amido and thiolate complexes were synthesized and compared to their previously reported Cu analogues as carbonyl hydroboration catalysts (IPr = bis(2, 6-diisopropylphenyl)imidazol-2-ylidene). Abstract : Three new IPr-Ag- and -Au-SNS amido and thiolate complexes were synthesized and compared to their previously reported Cu analogues as carbonyl hydroboration catalysts (IPr = bis(2, 6-diisopropylphenyl)imidazol-2-ylidene). Although these complexes showed no catalytic activity, treatment of the IPr-Ag-SNS amido complex with pinacolborane released the N -borylated ligand, S Me N Bpin S Me, (L 1 -Bpin ). This finding led us to reinvestigate the IPr-Cu-SNS amido precatalyst, revealing that immediate loss of L 1 -Bpin converts our catalyst system to [CuH(IPr)]2 .